Conceptualizing women’s empowerment in agrifood systems governance: A new framework - Ragasa, Catherine; Kyle, Jordan; Kristjanson, Patricia M.; Eissler, Sarah (International Food Policy Research Institute, 2022)
This paper develops a new framework to measure and track women’s empowerment in governance of countries’ agrifood systems. All too often, women’s needs, priorities, and voices are missing from the policy process, even when women may be disproportionately affected by shocks or have distinct policy preferences. The Women’s Empowerment in Agrifood Systems Governance (WEAGov) is an assessment framework to help countries and stakeholders measure the extent of inclusion and leadership of women in agrifood systems governance and to identify gaps and opportunities for improvement. WEAGov looks across three stages of the policy cycle: policy design, policy implementation, and policy evaluation. At each stage of the policy cycle, WEAGov asks three questions central to women’s empowerment in governance: Are women considered? Are women included? And are women influencing? This paper describes the process of conceptualizing and developing the WEAGov assessment framework by drawing together evidence, experience, and lessons from the literature and from over 30 stakeholder consultations across several countries and sectors to develop a practical and theoretically grounded framework.